Reframing Tribal Planning–Re–Building Our Own Communities for Local Development. Issue 1 (2nd January 2023) - Trevan, Eric S.
ABSTRACT: Tribal planning is reframed in the second decade of the 21 st century adjusting to the changing environments of the planning field, recently grounded in economic development, as a catalyst for these changes. Tribal planning, when led by tribal citizens, is the catalyst for sovereign decision-making. With tribal nations identifying economic development as a priority and gateway toward prosperity, other essential functions of the government attached themselves to this opportunity. Planning when aligned with economic development is much broader than defining tribe communities' economic returns, but supporting the progress of a culture and developing all systems that influence the economy. The article examines the role of community, economic and cultural capitals to examine the planning capacity of tribal communities.